UJI ANTAGONIS BAKTERI TERHADAP CENDAWAN PATOGEN PENYAKIT BLAS - Zuraidah, Zuraidah; Nida, Qatrun; Wahyuni, Sri (Biotik, 2020)
Damage to leaves, panicles, and stems of rice plants caused by fungal pathogens, Pyricularia grisea, which causes Blas. Control of this disease by the use of biological agents in the form of bacteria which is Bacillus cereus and Pseudomonas aeruginosa, and consortium. This research aims to determine the ability of these bacterial isolates to inhibit the growth of Pyricularia grisea. This research was arranged in a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The working procedures in this research were sampling of pathogenic fungi, making Pyricularia grisea liquid inoculum, and testing bacterial antagonists for pathogenic fungi in vitro. Analysis of variance (ANAVA) was used, with Fcount = 802.66 and Ftable = 3.48 with a significant level of Î± = 0.05 (5%) proved that the isolates of the bacteria Bacillus cereus and Pseudomonas aeruginosa could play an antagonistic role towards the fungus Pyricularia grisea. The results of this research indicate that bacterial isolates were able to inhibit the growth of Pyricularia grisea by the formation of the largest average clear zone in the treatment of Bacillus cereus bacteria which was 9.57 mm. The clear zone in the fungicide is 9.53 mm, the consortium is 9.37 mm, and the Pseudomonas aeruginosa is 8.2 mm.